Automated one‐step radiosynthesis of the CB1 receptor imaging agent [18F]MK‐9470. (25th August 2014) - Thomae, David; Morley, Thomas J.; Hamill, Terence; Carroll, Vincent M.; Papin, Caroline; Twardy, Nicole M.; Lee, H. Sharon; Hargreaves, Richard; Baldwin, Ronald M.; Tamagnan, Gilles; Alagille, David
<x xml:space="preserve">Abstract</x> The fluorine‐18‐labeled positron emission tomography (PET) radiotracer [18F]MK‐9470 is a selective, high affinity inverse agonist that has been used to image the cannabinoid receptor type 1 in human brain in healthy and disease states. This report describes a simplified, one‐step [18F]radiofluorination approach using a GE TRACERlab FXFN module for the routine production of this tracer. The one‐step synthesis, by [18F]fluoride displacement of a primary tosylate precursor, gives a six‐fold increase in yield over the previous two‐step method employing O‐alkylation of a phenol precursor with 1, 2‐[18F]fluorobromoethane. The average radiochemical yield of [18F]MK‐9470 using the one‐step method was 30.3 ± 11.7% (n = 12), with specific activity in excess of 6 Ci/µmol and radiochemical purity of 97.2 ± 1.5% (n = 12), in less than 60 min. This simplified, high yielding, automated process was validated for routine GMP production of [18F]MK‐9470 for clinical studies.